Poly(N,N-dimethylacrylamide)-coated maghemite nanoparticles for stem cell labeling - Babic, Michal; Horák, Daniel; Jendelová, Pavla; Glogarová, Katerina; Herynek, Vít; Trchova, Miroslava; Likavanová, Katarína; Lesný, Petr; Pollert, Emil; Hájek, Milan; Syková, Eva (Bioconjugate chemistry, 2009)
Maghemite (gamma-Fe2O3) nanoparticles were obtained by the coprecipitation of Fe(II) and Fe (III) salts with ammonium hydroxide followed by oxidation with sodium hypochlorite. Solution radical polymerization of N,N-dimethylacrylamide(DMAAm) in the presence of maghemite nanoparticles yielded poly(N,N-dimethylacrylamide)(PDMAAm)-coated maghemite nanoparticles. The presence of PDMAAm on the maghemite particle surface was confirmed by elemental analysis and ATR FTIR spectroscopy. Other methods of nanoparticle characterization involved scanning and transmission electron microscopy, atomic adsorption spectroscopy (AAS), and dynamic light scattering (DLS). The conversion of DMAAm during polymerization and the molecular weight of PDMAAmbound to maghemite were determined by using gas and size-exclusion chromatography, respectively. The effect of ionic 4,4'-azobis(4-cyanovaleric acid) (ACVA) initiator on nanoparticle morphology was elucidated. The nanoparticles exhibited long-term colloidal stability in water or physiological buffer. Rat and human bone marrow mesenchymal stem cells (MSCs) were labeled with uncoated and PDMAAm-coated maghemite nanoparticles and with Endorem as a control. Uptake of the nanoparticles was evaluated by Prussian Blue staining, transmission electron microscopy, T(2)-MR relaxometry, and iron content analysis. Significant differences in labeling efficiency were found for human and rat cells. PDMAAm-modified nanoparticles demonstrated a higher efficiency of intracellular uptake into human cells in comparison with that of dextran-modified (Endorem) and unmodified nanoparticles. In gelatin, even a small number of labeled cells changed the contrast in MR images. PDMAAmcoatednanoparticles provided the highest T(2) relaxivity of all the investigated particles. In vivo MR imaging ofPDMAAm-modified iron oxide-labeled rMSCs implanted in a rat brain confirmed their better resolution compared with Endorem-labeled cells.
Keywords: Microscopy, Electron, Transmission; krysa rodu Rattus; radiační rozptyl; Gelatin; Mesenchymal Stem Cells; Scattering, Radiation; Humans; nanočástice; magnetická rezonanční tomografie; lidé; Staining and Labeling; barvení a značení; Rats; akrylamidy; Ferric Compounds; Magnetic Resonance Spectroscopy; želatina; magnetická rezonanční spektroskopie; Animals; Magnetic Resonance Imaging; zvířata; železité sloučeniny; viabilita buněk; spektroskopie infračervená s Fourierovou transformací; mezenchymální kmenové buňky; Spectroscopy, Fourier Transform Infrared; Nanoparticles; Cell Survival; transmisní elektronová mikroskopie; Acrylamides